Asteroid Lightcurves from the MOA-II Survey: a pilot study. Issue 2 (12th March 2022) - Cordwell, A J; Rattenbury, N J; Bannister, M T; Cowan, P; ,; Abe, Fumio; Barry, Richard; Bennett, David P; Bhattacharya, Aparna; Bond, Ian A; Fujii, Hirosane; Fukui, Akihiko; et al.
ABSTRACT: The Microlensing Observations in Astrophysics (MOA-II) survey has performed high cadence, wide field observations of the Galactic Bulge from New Zealand since 2005. The hourly cadence of the survey during eight months of the year, across nearly 50 deg 2 of sky, provides an opportunity to sample asteroid lightcurves in the broad MOA-R filter. We perform photometry of a subset of bright asteroids numbered observed by the survey. We obtain 26 asteroid rotation periods, including for two asteroids where no prior data exist, and present evidence for the possible non-principal axis rotation of (2011) Veteraniya. This archival search could be extended to several thousands of asteroids brighter than 22nd magnitude.